Разработка эффективных методов оптимизации сложных теплоутилизационных систем энергетическихустановок (часть 1) - Фиалко, Н. М.; Степанова, А. И.; Навродская, Р. А. (Energy and Automation, 2017)
DEVELOPMENT OF EFFECTIVE METHODS OPTIMIZATION COMPLEX HEAT RECOVERY SYSTEMS ENERGY INSTALLATIONS (PART 2) N. Fialko, А. Stepanovа R. Navrodska The insufficient level of utilization of thermal secondary energy resources in Ukraine is mainly due to the low efficiency of heat recovery equipment. At the same time, it is known that Ukraine has the necessary potential for implementing effective technologies for heat recovery, and therefore the problem of their development and implementation is relevant both now and in the near future. The aim of the work is the development of effective optimization methods for complex heat recovery systems of boiler plants based on the principles of the structural-variant approach. For complex heat recovery systems that include a large number of elements, it is not possible to establish general analytical dependencies of the optimization objective functions on the parameters of the system when building mathematical models necessary for their optimization. In these cases, it is advisable to develop effective optimization methods for such systems based on the basic principles of the structural-variant approach to optimization. In this paper, the main stages of development for complex heat recovery systems of an optimization method based on the principles of a structurally-variant approach are considered using examples of heat recovery systems of boiler plants. The basic principles of the structural-variant approach used in the work are as follows: • to develop a structural scheme of the installation, consisting of a number of discrete interconnected streams of elements of a simple structure; • to conduct thermal and exergetic calculations for the recognition of elements, a change in the loss of exergy power in which the most significant effect on the change in the efficiency of the installation as a whole; • Optimize the selected elements using certain methods, for example, balance methods of exergic analysis and statistical methods of experiment planning; • to introduce optimized elements into the general schemes of installations; • use the following optimization steps to obtain the values of the optimal parameters of individual elements as initial conditions. In accordance with these principles, structural schemes have been developed for various heat recovery systems of boiler plants, consisting of a number of discrete, interconnected by exergy flows elements of a simple structure. In complex thermodynamic systems, there is always an element or set of elements, the change in the loss of exergy power in which most significantly affects the change in the efficiency of the system as a whole. In accordance with the principles of the structural-variant method, such elements need to be optimized and introduced into the general schemes of installations. This allows us to more deeply analyze the operation of the installation as a whole and improve the accuracy of the solution of the overall optimization problem by using, as initial conditions, the already obtained values of the optimal parameters of the individual elements and refining these values in the process of solving the optimization problem. For the schemes presented in the paper, a series of thermal and exergetic calculations was carried out, which are intended to show to what extent the change in the loss of exergy power in individual elements of the installation affects the overall efficiency of the installation. As a result of calculations, the elements are determined, the change in the loss of exergy power in which most significantly affects the change in the efficiency of the installations as a whole. Further, in accordance with the basic principles of the structural-variant approach, optimization of these elements is carried out. To this end, using the balance methods of exergic analysis and statistical methods of experiment planning, functional dependencies of the exergo-technological and heat-exergy criteria of efficiency evaluation were obtained, which served as optimization objective functions, from the geometric parameters of the heat exchange surface of these elements. Areas of their optimal values obtained by minimizing the corresponding functional dependencies are determined. The elements optimized in this way are introduced into the general scheme of the installations, and the obtained optimum values of the geometric parameters of the heat exchange surface are used in the next stages of optimization as initial conditions. Thus, based on the principles of a structurally-variant approach to optimization, an optimization method was developed for complex heat recovery systems of boiler units, within the framework of which structural schemes were constructed with the indication of exergic flows between elements of a simple structure. A series of thermal and exergetic calculations was carried out, which made it possible to determine the elements, the change in the losses of exergic power in which most significantly affects the change in the efficiency of the installations as a whole. With the help of balance methods of exergic analysis and statistical methods of experiment planning for these elements, functional dependences of the optimization objective functions on the geometric parameters of the heat exchange surface were obtained and the regions of their optimum values were determined. The elements optimized in this way are introduced into the general schemes of the plants, and the optimum values of the geometric parameters of the heat exchange surface are used in the next stages of optimization as initial conditions.